ISSP position stand: competent supervision in sport psychology - Poczwardowski, A.; Andersen, M. B.; Van Raalte, J. L.; Harwood, C.; Si, G.; Tshube, T.; Noce, F. (International Journal of Sport and Exercise Psychology, 2023)
Supervision enhances professional functioning, helps ensure quality services, and fills a gatekeeping function for the profession. This International Society of Sport Psychology (ISSP) Position Stand synthesises the most pertinent literature on supervision practices relevant to sport psychology (SP), builds on the collective supervision experience of the authors and the present ISSP Managing Council, and offers recommendations for competent, ethical, and culturally safe supervision. Specifically, after defining supervision and describing supervision models and their relational features, we review the scholarly contributions in the areas of supervision content and methods (including tele-supervision), along with cultural, linguistic, ethical, and legal considerations. We conclude with a set of nine postulates that are further operationalised through recommendations for competent supervision practices.